Purpose, Quality, and Value in Critical Realist Research within Nurse Education - Coleman, Phil (Nurse Media Journal of Nursing, 2019)
Background: There have been a wide range of practice fields in nursing research including education; however, the quality of research in these disciplines has often failed to provide a sufficiently robust foundation.     Purpose: This paper explores the purpose of educational research, how quality can be assured in such research and how the value of a research study in nurse education can be determined; focusing predominantly on arguments associated with the use of qualitative, and to a lesser extent, mixed methods research.  Methods: A Critical Realist review drawing upon relevant literature from the fields of nursing, education, and healthcare was undertaken to examine issues of purpose, quality, and value in such research.Results: A wide range of criteria were identified to evaluate the purpose, quality, and value of Critical Realist research using qualitative and mixed methods research within nurse education.Conclusion: The holistic, theoretically-eclectic, pragmatic, and solution-focused nature of nursing as a discipline means that Critical Realist research in nursing, and more specifically, nurse education should explicitly reflect these principles.